Audit Committee as a Moderator of Audit Report Lag Determinants: Evidence from Indonesian Metal and Mineral Firms (2021–2024) - Ivana Rimba; Riswan Yudhi Fahrianta; Jumirin Asyikin; Sri Ernawati (Politeknik Ganesha Medan, 2026)
This study empirically examines firm size, audit opinion, audit tenure, and profitability effects on audit report lag (ARL), while exploring audit committee moderating roles. Research concentrates on metal and mineral sector corporations, an industry where financial reporting timeliness is essential for sustaining investor confidence and meeting Indonesia's 90-day regulatory requirement. Study population comprises all metal and mineral corporations listed on Indonesia Stock Exchange during 2021-2024. Employing purposive sampling methodology based on predetermined criteria, 24 corporations were selected, producing 96 firm-year observations. Quantitative research methodology utilized secondary data obtained from published annual financial statements. ARL is measured as the number of days between fiscal year-end and audit report date. Data analysis employed multiple linear regression and Moderated Regression Analysis for evaluating direct and interaction effects. Findings reveal firm size exerts negative yet insignificant effects on ARL, whereas audit opinion, audit tenure, and profitability demonstrate negative and significant influences on audit completion timeliness. Additionally, audit committees strengthen firm size-ARL relationship; nevertheless, they fail moderating audit opinion, audit tenure or profitability-ARL relationships. This study contributes by clarifying the selective role of audit committee monitoring: while it strengthens the firm size-ARL relationship through intensified oversight in large firms, it does not moderate the effects of audit opinion, audit tenure, or profitability on reporting timeliness.Overall, results indicate internal financial performance and external audit characteristics perform critical roles in determining reporting timeliness, emphasizing the importance of optimizing audit committee oversight functions for minimizing audit delays and enhancing financial reporting reliability.